Comparison of traditional and intrafascial iliac crest bone-graft harvesting in lumbar spinal surgery - (:unkn) unknown (SPRINGER, 2004)
We studied 117 adult patients undergoing posterior lumbar spinal fusion and instrumentation using bone grafts from the iliac crest between February 1999 and January 2001. All patients had degenerative disease of the lumbar spine, and all were operated upon by the same surgeon. Patients were randomized to have the iliac bone graft harvested either through a separate incision (traditional approach) or utilizing the same inidline incision as used for the spinal surgery (intrafascial approach). Total volume of harvested graft, blood loss, pain, complications, and patient satisfaction were evaluated with a minimum of 2-year follow-up. There were no infections. The average volume of harvested bone was 17.2 cc versus 14.7 cc; total blood loss was 168 cc versus 96 cc; total complication rate was 20% versus 8%, and overall satisfaction rate was 81 % versus 96%, respectively. The intrafascial graft harvesting technique minimizes morbidity and increases patient satisfaction compared with the traditional bone harvesting technique.
Keywords: SITE MORBIDITY; COMPLICATIONS